Spatial Hydrological GIS Analysis and Estimations of Runoff in Khor Gowb Drainage Basin in the Red Sea State –Sudan (University of Khartoum Engineering Journal, 2022)
The magnitude and availability of surface waters in Khor Gwob of the Red Sea State was examinedusing spatial hydrological analysis in Geographical Information Systems (GIS). As a system with advanced geo-modelling capabilities, GIS is used to integrate spatial analysis with hydrological modelling. Several levels ofspatial hydrological modelling such as parameterization, spatial integration, regionalization and assessment ofhydrologic problems were made. Four physical / deterministic and stochastic models were developed and appliedat both catchment‟s and regional scales to estimate the water volume of many drainage basins in the area. Theresults evaluated using the general error term to compute the differences between the estimated areal runoff andthe observed runoff in the Khor Gwob drainage basin in Erkowit area of the Red Sea State. Accordingly, onestochastic model has been tested and regionalized. The significance of the catchment and regional runoff estimateswas evaluated in relation to errors inherent in the spatial database, GIS analysis, and hydrological modelling (e.g.,the Rational Formula). Finally, it is concluded that Khor Gwob basin and the Red Sea State at large, contributes anannual surface runoff that exceeds the human and animal needs with a considerable surplus that can be used foragriculture (i.e., the region is water sufficient). Conversely, this sufficiency is limited by the problem of spatialdistribution and related storage difficulties. With regard to human, animal and agricultural water supply, only fewcatchments can support the proposition of water sufficiency in the State.